Socialization at Public Junior High School 1 Pamarayan regarding the Dangers of Narcotics Abuse among the Younger Generation - Amilia, Euis; Rosdiyani, Telly; Artiwi, Nila Prasetyo; Rusmana, Indra Martha; Afliyah, Savika (Indonesian Journal of Community Services Cel, 2023)
The cases of narcotics and illegal drugs abuse among the younger generation have been increasing and could impede the sustainability of Indonesia’s young population in the future. Therefore, efforts to protect the younger generation from these issues are highly necessary. The socialization activity at Public Junior High School 1 Pamarayan, Serang Regency regarding the dangers and impacts of narcotis abuse aimed to help participants understand the impact of narcotics abuse, namely physical, psychological, and socio-economic impacts. This activity applied lecture and participatory discussion method using PowerPoint slides, organized by the university students from community services Group 15 Kampungbaru Village, Pamarayan. The speaker (resource person) in this socialization was the staff from National Narcotics Agency, Serang Regency. This activity was conducted on September 4, 2023, attended by a total of 51 participants. The results reveal that the socialization has positively contributed in increasing students’ knowledge and understanding of the dangers and impacts of narcotics abuse, as proven by the number of students who actively participated and became more aware about the dangers of narcotics. This socialization is expected to be a solid foundation to fortify the younger generation as Indonesia’s next generation, especially students at Public Junior High School 1 Pamarayan, from the dangers of narcotics abuse